2007
DOI: 10.1111/j.1365-2982.2007.00996.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mosapride citrate on proximal and distal colonic motor function in the guinea‐pig in vitro

Abstract: Mosapride citrate (mosapride), a substituted benzamide, is a selective 5-HT(4) receptor agonist, and is known to have prokinetic properties on the stomach. However, it is unclear whether mosapride also has a prokinetic effect on the colon. We previously found that mosapride significantly shortened colonic transit time in the guinea-pig, an animal with a distribution of colonic 5-HT(4) receptors similar to that of a human. So, we aimed to separately evaluate the effect of mosapride on proximal and distal coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 15 publications
3
21
0
1
Order By: Relevance
“…This result differed from the primary data on mosapride (Table 1). We also found that mosapride significantly increased contractile amplitude in the proximal colon, coinciding with rapid transit (Kim et al, 2008). This increased contraction might physiologically expel the proximal stored contents into the distal portion.…”
Section: The Effect Of 5-ht4 Receptor Agonists On Colonic Motor Functionsupporting
confidence: 62%
See 1 more Smart Citation
“…This result differed from the primary data on mosapride (Table 1). We also found that mosapride significantly increased contractile amplitude in the proximal colon, coinciding with rapid transit (Kim et al, 2008). This increased contraction might physiologically expel the proximal stored contents into the distal portion.…”
Section: The Effect Of 5-ht4 Receptor Agonists On Colonic Motor Functionsupporting
confidence: 62%
“…The localization of 5-HT4 receptors in the human colon shows the same pattern as that in the guinea pig (Sakurai-Yamashita et al, 1999). 5-HT4 receptors are more densely distributed in the myenteric plexus in the proximal colon than in the distal colon (Kim et al, 2008). However, in circular muscle, the receptors are more abundant in the distal colon than in the proximal colon.…”
Section: Different Functions Of the Proximal And Distal Colonsupporting
confidence: 52%
“…16 A baseline 1 g of tension was loaded onto the circular muscle strip during the 60 minutes equilibrium period. 17,18 Electrical field stimulation was conducted to estimate contraction of each organ using a stimulator (Grass S88; Astro-Med, West Warwick, RI, USA). Based on the methods used in other studies, the detailed conditions of electrical field stimulation were as follows: antrum (1 millisecond pulse duration, 80 V, for 10 seconds); jejunum (1 millisecond pulse duration, 60 V, for 10 seconds); ileum (0.5 milliseconds pulse duration, 60 V, for 10 seconds); and proximal colon (0.5 milliseconds pulse duration, 60 V, for 10 seconds) in a stepwise-increment of frequency (2,4,8,and 16 Hz).…”
Section: Measurement Of Contractile Activity Through a Tissue Bath Studymentioning
confidence: 99%
“…It is reported that mosapride administered intragastrically at doses of 3 -30 mg/kg significantly enhances colonic motility in conscious guinea pigs implanted with force transducers (21). It is also reported that mosapride accelerates proximal and distal colonic transit or peristalsis in vitro in guinea pigs (23). These results indicate that the stimulatory effect of mosapride on colonic transit is due to accelerated colonic motility and peristalsis in guinea pigs.…”
Section: Discussionmentioning
confidence: 80%